2014
DOI: 10.1038/nchem.1945
|View full text |Cite|
|
Sign up to set email alerts
|

A transferable model for singlet-fission kinetics

Abstract: Exciton fission is a process that occurs in certain organic materials whereby one singlet exciton splits into two independent triplets. In photovoltaic devices these two triplet excitons can each generate an electron, producing quantum yields per photon of >100% and potentially enabling single-junction power efficiencies above 40%. Here, we measure fission dynamics using ultrafast photoinduced absorption and present a first-principles expression that successfully reproduces the fission rate in materials with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

36
527
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 427 publications
(572 citation statements)
references
References 47 publications
36
527
4
5
Order By: Relevance
“…Because the triplets produced are coupled into an overall singlet state, spin is conserved and triplet formation can proceed on sub-100-fs timescales (1,(3)(4)(5) with yields of up to 200% (1,6,7). Current interest in singlet fission is driven by its potential to improve the efficiency of solar cells by circumventing the Shockley-Queisser limit for single-junction devices (8)(9)(10).…”
mentioning
confidence: 99%
“…Because the triplets produced are coupled into an overall singlet state, spin is conserved and triplet formation can proceed on sub-100-fs timescales (1,(3)(4)(5) with yields of up to 200% (1,6,7). Current interest in singlet fission is driven by its potential to improve the efficiency of solar cells by circumventing the Shockley-Queisser limit for single-junction devices (8)(9)(10).…”
mentioning
confidence: 99%
“…Only the generation of two triplets is allowed. [11][12][13][14] Thus, singlet exciton fission in neat films of tetracene competes only with the relatively slow processes of singlet exciton fluorescence and nonradiative decay to the ground state. Indeed, multiple studies have shown or suggested a near unity efficiency for the fission process in neat films of tetracene.…”
mentioning
confidence: 99%
“…2(a). 10,14 For comparison, we build devices from tetracene and pentacene using C 60 in both cases as an acceptor molecule. Fission is exothermic and significantly faster in pentacene, allowing us to study the impact of the fission rate on its yield in devices.…”
mentioning
confidence: 99%
“…Additionally, past experiments in single-crystal, polycrystalline, and amorphous solids of pentacene have documented that the efficiency of SF relates to the electronic coupling between these two chromophores (8,9). Hence, molecular ordering in terms of crystal packing, that is, proximity, distances, orbital overlap, etc., is decisive with respect to gaining full control over and to finetuning interchromophoric interactions in the solid state (10,11). Of equal importance are the thermodynamic requirements, namely that the energy of the lowest-lying singlet absorbing state must match or exceed the energy of two triplet excited states (S 1 ≥ 2T 1 ) (11).…”
mentioning
confidence: 99%
“…Hence, molecular ordering in terms of crystal packing, that is, proximity, distances, orbital overlap, etc., is decisive with respect to gaining full control over and to finetuning interchromophoric interactions in the solid state (10,11). Of equal importance are the thermodynamic requirements, namely that the energy of the lowest-lying singlet absorbing state must match or exceed the energy of two triplet excited states (S 1 ≥ 2T 1 ) (11). In light of both aspects, hydrocarbons such as acenes--tetracene, pentacene, hexacene--and their derivatives are at the forefront of investigations toward a sound understanding and development of molecular building blocks for SF.…”
mentioning
confidence: 99%